Chlamydiaphage φCPG1 Capsid Protein Vp1 Inhibits Chlamydia trachomatis Growth via the Mitogen-Activated Protein Kinase Pathway - Guo, Yuanli (Viruses, 2016)
Chlamydia trachomatis is the most common cause of curable bacterial sexually transmitted infections worldwide. Although the pathogen is well established, the pathogenic mechanisms remain unclear. Given the current challenges of antibiotic resistance and blocked processes of vaccine development, the use of a specific chlamydiaphage may be a new treatment solution. φCPG1 is a lytic phage specific for Chlamydia caviae, and shows over 90% nucleotide sequence identity with other chlamydiaphages. Vp1 is the major capsid protein of φCPG1. Purified Vp1 was previously confirmed to inhibit Chlamydia trachomatis growth. We here report the first attempt at exploring the relationship between Vp1-treated C. trachomatis and the protein and gene levels of the mitogen-activated/extracellular regulated protein kinase (MAPK/ERK) pathway by Western blotting and real-time PCR, respectively. Moreover, we evaluated the levels of pro-inflammatory cytokines interleukin (IL)-8 and IL-1 by enzyme-linked immunosorbent assay after Vp1 treatment. After 48 h of incubation, the p-ERK level of the Vp1-treated group decreased compared with that of the Chlamydia infection group. Accordingly, ERK1 and ERK2 mRNA expression levels of the Vp1-treated group also decreased compared with the Chlamydia infection group. IL-8 and IL-1 levels were also decreased after Vp1 treatment compared with the untreated group. Our results demonstrate that the inhibition effect of the chlamydiaphage φCPG1 capsid protein Vp1 on C. trachomatis is associated with the MAPK pathway, and inhibits production of the pro-inflammatory cytokines IL-8 and IL-1. The bacteriophages may provide insight into a new signaling transduction mechanism to influence their hosts, in addition to bacteriolysis.